Pengaruh Employee-Generated Content pada Aplikasi Tiktok terhadap Kepercayaan Konsumen Produk Aerostreet - Rio Dody Christanto; Indah Handaruwati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid growth of social media has encouraged companies to implement more interactive marketing strategies to build consumer trust. One strategy that has recently emerged is Employee Generated Content (EGC), which is content created and shared by employees through digital platforms such as TikTok. This type of content is considered more authentic and credible than traditional promotions. This study aims to analyze the influence of employee-generated content on TikTok on consumer trust in Aerostreet products. The research approach used is quantitative with a positive philosophy. Data were obtained through an online questionnaire distributed to 40 active TikTok respondents who had viewed employee content related to Aerostreet products, using a purposive sampling technique. The analysis was conducted using multiple linear regression assisted by statistical software. The results showed that partially, company credibility and content quality did not have a significant influence on consumer trust, while creator creativity was proven to have a positive and significant influence. Simultaneously, these three variables had a significant influence on consumer trust. The coefficient of determination showed that 93.6% of the variation in consumer trust was explained by the three independent variables, while the remaining 6.4% was influenced by other factors outside this study. These findings confirm that creativity in delivering employee-generated content on TikTok plays a significant role in capturing audience attention and increasing consumer trust in the Aerostreet brand.